The Iron Age II tombs of area E, Tel Achiv: between local traditions and the consolidation of the tyrian polity - Edrey, Meir (Israel exploration journal, 2018)
During the 1963 excavation season at Tel Achziv, directed by M.W. Prausnitz, three cist tombs were unearthed in Area E, on the eastern part of the mound. These tombs, built of large roughly-hewn stone blocks, previously dated to the Iron Age IB, display a rich material culture, consisting of pottery vessels, weapons, jewellery and other small finds. To date, only parts of the assemblage of these tombs have been published in preliminary publications. Here, for the first time, we consider the entirety of the tomb assemblages, including ceramic, metal and other finds, as well as tomb architecture and human remains. We maintain that the emerging picture points to a more complex narrative of the Iron Age settlement at Achziv and its population than previously thought. Rather than dating to the Iron IB, they can be related to the Iron IIA and to the existence of an elite manifesting its local identity through burial practices reflecting long-lasting coastal cultural traditions. At the same time, a new date for the resettlement of Achziv is offered and connected to processes of Tyrian consolidation of power, accompanied by the establishment of administrative control in parts of the western Galilee and the Akko Valley in the Iron Age IIA.